The mechanisms and diagnostic potential of lncRNAs, miRNAs, and their related signaling pathways in cervical cancer - Xu, Yan; Sun, Yu; Song, Xiaobin; Ren, Jian (Frontiers in Cell and Developmental Biology, 2023)
Cervical cancer (CC), the fourth most prevalent cancer type among women worldwide, has high morbidity and mortality. Due to the long latent period of CC, most patients are already in the middle to late stages when initially diagnosed, which greatly reduces the clinical cure rate and survival quality, thus resulting in poor outcomes. In recent years, with the continuous exploration in the field of bioinformatics and molecules, it has been found that ncRNAs including miRNAs and lncRNAs without ability to translate proteins are capable to activate or inhibit certain signaling pathways by targeting and modulating the expression level of proteins involved in signaling pathways. NcRNAs play important roles in assisting diagnosis, drug administration and prognosis prediction during CC progression. The mechanism of interaction between miRNAs, lncRNAs and signaling pathway as the entry point has been carried out for a long time in the basic research of CC, and abundant experimental studies have confirmed the close relation of miRNA and lncRNA-signaling pathways with CC development. Therefore, we summarized the latest advances on the involvement of lncRNA- and miRNA-related signaling pathways in the development of CC for providing guidance in CC treatment.